2011
DOI: 10.1007/s00044-011-9562-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated xanthones: antiproliferative effects and enhancement of the growth inhibitory action of 4-hydroxytamoxifen in estrogen receptor-positive breast cancer cell line

Abstract: The effects of three prenylated xanthones on the in vitro growth of estrogen-dependent ER (?) MCF-7 (breast), estrogen-independent ER (-) MDA-MB-231 cells (breast), and NCI-H460 (non-small cell lung) were investigated in a complete and/or steroid-free medium. 3,4-Dihydro-12-hydroxy-2,2-dimethyl-2H,6H-pyrano[3,2-b]xanthen-6-one (4), the most potent against the ER(?) MCF-7 cell line (GI 50 = 5 lM), showed an enhancement in the anti-estrogenic effect of 4-hydroxytamoxifen in this ER(?) cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Prenylated xanthones 4-dihydro-12-hydroxy-2,2-dimethyl-2H,6H-pyrano [3,2-b]xanthone, 3, 4-bis-(3-methylbut-2-enyloxy)-xanthone, and 3-(3-methylbut-2-enyloxy)-4-hydroxy-xanthone were obtained as described elsewhere. 29 The synthesis of the following thioxanthone derivatives was performed according to described procedures: 32 1-((2-(phenylamino)ethyl)amino)-4-propoxythioxanthone, 1-((3,5-dimethoxyphenyl)amino)-4-hydroxythioxanthone, 1-((3,4-dimethoxybenzyl)amino)-4-propoxythioxanthone, 1-((3,4,5-trimethoxyphenyl)amino)-4-propoxythioxanthone, 1-(piperidin-1-yl)-4-propoxythioxanthone (9), 1-(2-(1H-benzimidazol-2-yl)ethanamine)-4-propoxythioxanthone, 1-((2-(1,3-benzodioxol-5-yl)ethyl)amino)-4-propoxythioxanthone, 1-((2-(diethylamino)ethyl)amino)-4-propoxythioxanthone (10), 1-methoxy-4-propoxythioxanthone (11), 1-(isobutylamino)-4-propoxythioxanthone, and 1-(isopropylamino)-4-propoxythioxanthone.…”
Section: Chemistrymentioning
confidence: 97%
“…Prenylated xanthones 4-dihydro-12-hydroxy-2,2-dimethyl-2H,6H-pyrano [3,2-b]xanthone, 3, 4-bis-(3-methylbut-2-enyloxy)-xanthone, and 3-(3-methylbut-2-enyloxy)-4-hydroxy-xanthone were obtained as described elsewhere. 29 The synthesis of the following thioxanthone derivatives was performed according to described procedures: 32 1-((2-(phenylamino)ethyl)amino)-4-propoxythioxanthone, 1-((3,5-dimethoxyphenyl)amino)-4-hydroxythioxanthone, 1-((3,4-dimethoxybenzyl)amino)-4-propoxythioxanthone, 1-((3,4,5-trimethoxyphenyl)amino)-4-propoxythioxanthone, 1-(piperidin-1-yl)-4-propoxythioxanthone (9), 1-(2-(1H-benzimidazol-2-yl)ethanamine)-4-propoxythioxanthone, 1-((2-(1,3-benzodioxol-5-yl)ethyl)amino)-4-propoxythioxanthone, 1-((2-(diethylamino)ethyl)amino)-4-propoxythioxanthone (10), 1-methoxy-4-propoxythioxanthone (11), 1-(isobutylamino)-4-propoxythioxanthone, and 1-(isopropylamino)-4-propoxythioxanthone.…”
Section: Chemistrymentioning
confidence: 97%
“…The biological activity of xanthones and their derivatives is based on their tricyclic scaffold but depends on the nature and position of the different substituents [2] . Since xanthones may play a role as anti-proliferative and pro-apoptotic agents [2] , [11] , [12] , [13] , [14] , several derivatives, including (thio)xanthone derivatives, have been synthesized and tested in human cancer cell lines [14] , [15] , but not in fungi. It is thus important to add data from different organisms to the current knowledge on the mechanism of action of xanthones.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a dihydropyranoxanthone, synthetized by some of us, 3,4-dihydro-12-hydroxy-2,2-dimethyl-2H,6H-pyrano[3,2-b]xanthen-6-one (1, Fig. 1), presented significant antiproliferative and apoptotic inducing effects (Paiva et al, 2012;Palmeira et al, 2010) in human tumor cell lines. Both ␣-mangostin (Leão et al, 2013a) and compound 1 (Leão et al, 2013b) were shown to be promising inhibitors of p53-MDM2 interaction, with compound 1 showing the highest inhibitory activity in a yeast target-based assay, mimicking the activity of known p53 activators.…”
Section: Introductionmentioning
confidence: 99%